Hermeneutics: an introduction - Thiselton, Anthony C. (W. B. Eerdmans Publ. Company, 2009)
Anthony Thiselton here brings together his encyclopedic knowledge of hermeneutics and his nearly four decades of teaching on the subject to provide an splendid interdisciplinary textbook. After a thorough historical overview of hermeneutics, Thiselton moves into modern times with extensive analysis of scholarship from the mid-twentieth century, including liberation and feminist theologies, reader-response and reception theory, and postmodernism. No other text on hermeneutics covers the range of writers and subjects discussed in Thiselton's Hermeneutics.